(untitled) (Research, Society and Development, 2022)
Objective: To identify the main factors associated with falls in elderly inpatients in the scientific literature. Method: We conducted an integrative literature review with searches in the following databases: MedLine via VHL, PubMed, SciELO, Web of Science, Scopus, and LILACS. We identified 2,969 publications, of which 11 were selected for the final sample of this study. We built a theoretical model for the critical analysis and data presentation. The factors that presented association or risk for falls in elderly inpatients were considered as evidence. Results: The factors associated with falls in elderly inpatients were categorized into intrinsic and extrinsic. The main intrinsic factors identified were: 1) functional decline, delirium, history of falls, and advanced age; and the extrinsic factors: admission to a surgical ward and the use of central nervous system depressants, more precisely sedatives and antipsychotics. We observed that these factors are associated in the studied population. Conclusion: The studies showed that intrinsic factors are the main risk factors for falls in hospitalized elderly. However, we observed their association with extrinsic factors and the complexity of falls. Thus, these findings highlight the importance of multidimensional assessment of hospitalized elderly, the adoption of fall prevention strategies and timely intervention on modifiable factors, providing more safety to the elderly patient in the hospital environment.